Political positions of far right movements in Georgian reality - Tabatadze, Sandro (Politics / პოლიტიკა; 2020: მეორე ნომერი, 2020)
The article deals with the far right movement foundation process in Georgia, where Europeanization process still takes place. Study aims to determine how European understanding of radical/extreme right meets the Georgian reality in this point of view. Research focus on major and most visible political groups – “Georgian March”, “Georgian National Unity”, “Anti-liberals” and “Edelweiss”.  The article tries to formulate the relevant questionnaire to measure the essential features of these movement in the erms of political positions on foreign, domestic, social-ethical, identity policies. Also, it can be examined how the major members of these movements evaluate neo-populist and principle of rule of law. Conclusion includes the comparative analysis and linkages between these political movements.
Keywords: Far right, political movements, political positions, Georgian politics.